Isolated Osseous Excision in the Adult Carpus: A Narrative Review - Dolan, Joshua D.; Shiver, Luke; Wallace, Doyle; Whitehead, Jonathon; Wood, Matthew; Fulcher, S. Mark (Journal of Hand and Microsurgery, 2023)
Various pathologies of the adult carpus result in clinical scenarios where excision can be considered and even recommended. In the appropriate patient population, isolated carpal excision can alleviate pain and improve mobility. Excisions of the pisiform, trapezium, and trapezoid have abundant literature evidence to support positive long-term functional outcomes. In contrast, isolated excision of the capitate, hamate, and triquetrum has limited support in the literature secondary to compromise of carpal mechanics and lead to recurrent pain. Additionally, isolated scaphoid and lunate excision are best avoided secondary to carpal collapse and should be paired with concomitant stabilizing procedures in the carpus. This article provides a comprehensive literature review of isolated excision of each osseous carpal bone, their indications, and previously assessed outcomes.
Keywords: capitate; carpal bone; carpal excision; lunate; scaphoid; trapezium; wrist surgery